Initial Treatment, Sublimation Drying and Storage Time of Sweet Pepper Crisps. Microbiological Quality − Part II (Agricultural Engineering, 2020)
The paper presents the impact of the initial processing, cultivar, and storage time on the physical and chemical quality of freeze-dried sweet pepper crisps. Sweet pepper after initial washing and crushing was subjected to further four combinations of the initial processing. The first combination included freezing, the second one blanching in 98°C and 2-minutes time, the third one -dehydration in 2% solution of ascorbic acid and the fourth one - dehydration in the 2% solution of sodium chlo-ride. Both types of dehydration were carried out in 70°C for 20 minutes with a 1:4 participation of raw material to osmotic solution. Blanched and dehydrated raw materials were subjected to freezing in -18°C for 24 hours. After the completed process of freezing, the samples were moved to a freezer-drier and were dried by sublimation in -18°C and the reduced pressure of 63 Pa. The research that was carried out proved that the microbiological quality of the obtained sweet pepper lyophilizes was significantly affected by the cultivar, treatment type and storage time. These factors significantly diversified the number of micro-organisms in sweet pepper crisps. No initial processing before sublimation drying caused a considerably average increase of the number of psychrophile and mesophilic bacteria in crisps from both sweet pepper cultivars. A considerable reduction of their total number took place during blanching and dehydration in the ascorbic acid solution and sodium chloride solution. Additionally, along with the storage time, reduction of the total number of psychrophilic, mesophilic bacteria, fungi and yeasts was reported.